Takayasu Disease – Dominant Ectatic Epicardial Coronary ArterialInvolvement - Alhad Mulkalwar; T Jadhav; J Savla; P Vaideeswar (Tropical Journal of Pathology and Microbiology, 2022)
Takayasu arteritis (TA), also known as pulseless disease, occlusive thromboaortopathy, and Martorellsyndrome is a well known yet rare form of large vessel vasculitis, where an autoimmuneinflammation targets the aorta and its branches,1 typically in young women of reproductive age.2Coronary arterial involvement in TA is rare (to the extent of 11 %) manifesting as coronary ostialstenosis or occlusion and even more uncommonly as coronary arterial aneurysms.3